Development of the composition and research of the equivalence of suppositories with diclofenac sodium by in vitro method using “Dissolution” test for lipophilic solid dosage forms - Salii, О. O.; Baula, О. P.; Kharytonenko, A. I.; Fukleva, L. A.; Kyryliuk, А. S.; Салій, О. О.; Баула, О. П.; Харитоненко, А. І.; Фуклева, Лариса Анатоліївна; Кирилюк, А. С.; Салий, Е. А.; Харитоненко, А. И.; et al. (Запорізький державний медичний університет, 2019)
The aim. Development of the composition and investigation of the equivalence of suppositories with sodium diclofenac by in vitro method on a device with a flow-through cell in accordance with modern requirements of SPhU. Materials and methods. The development of the suppository composition was carried out with the use of the substance of diclofenac sodium and the excipient of solid fat of various grades. Studies of the active ingredient release in vitro in comparison with the reference listed drug were carried out on a device with a flow-through cell according to the monograph SPhU 2.9.42. Results.The investigations of the physical-chemical properties of the diclofenac sodium substance (micronisation, solubility) and the basis of the solid fat carrier, which affect the release of the active ingredient from the drug formulation were carried. The «particle size» figure for 2 samples of the active ingredient was from 100 to 400 μm and not more than 15 μm, respectively. The optimal composition of suppositories was developed by the method of 2-factor experiments. The conditions for the «Dissolution» test were determined: the volume of the medium (720 ml), the dissolution temperature (37.0 ± 0.5) ºC, the time taken for sampling (15, 30, 45, 60, 90 min), the dissolution medium – buffered solution with a pH of 7.4. The calculated similarity factor f2 was 67, which indicates the similarity of the release profiles and the equivalence of the researched drug. Conclusions. The pharmaco-technological properties of sodium diclofenac and the solid fat auxiliary substance were studied. A method for the release of sodium diclofenac with the use of a device with a flow-through cell in accordance with the requirements of the SPhU is developed. The level of release of sodium diclofenac in the dissolution medium from rectal suppositories was determined by the experimental method, as the first step in the bioavailability determination. The equivalence of the tested samples of suppositories with the reference listed drug with the help of the method in vitro was established. Мета роботи – розроблення складу та дослідження еквівалентності супозиторіїв із диклофенаком натрію методом in vitro на приладі з проточною коміркою згідно з сучасними вимогами ДФУ. Матеріали та методи. Розроблення складу супозиторіїв здійснили з застосуванням субстанції диклофенаку натрію та допоміжної речовини твердий жир різних марок. Дослідження вивільнення діючої речовини in vitro порівняно з референтним препаратом виконали на приладі з проточною коміркою відповідно до сучасних вимог ДФУ 2.9.42. Результати. Провели дослідження фізико-хімічних характеристик субстанції диклофенаку натрію (мікронізація, розчинність) та основи носія твердий жир, що впливають на вивільнення діючої речовини з лікарської форми. Показник «розмір часток» для двох зразків діючої речовини становив від 100 до 400 мкм і не більше ніж 15 мкм відповідно. Методом двофакторного експерименту розроблено оптимальний склад супозиторіїв. Визначили умови тесту «Розчинення»: об’єм середовища (720 мл), температура розчинення (37,0 ± 0,5) ºC, час відбору проб (15, 30, 45, 60, 90 хв), середовище розчинення – буферний розчин із рН 7,4. Розрахований коефіцієнт подібності f2 становив 67, що засвідчує подібність профілів вивільнення та еквівалентності дослідного препарату. Висновки. Дослідили фармако-технологічні властивості диклофенаку натрію та допоміжної речовини твердий жир. Розроблено методику вивільнення диклофенаку натрію з використанням приладу з проточною коміркою відповідно до вимог ДФУ. Експериментальним шляхом встановили ступінь вивільнення диклофенаку натрію в середовищі розчинення з супозиторіїв ректальних як перший етап визначення біодоступності. Встановили еквівалентність досліджуваних зразків супозиторіїв із референтним препаратом методом in vitro. Цель работы – разработка состава и исследования эквивалентности суппозиториев с диклофенаком натрия методом in vitro на приборе с проточной кюветой в соответствии с современными требованиями ГФУ. Материалы и методы. Разработку состава суппозиториев проводили с использованием субстанции диклофенака натрия и вспомогательного вещества твердый жир различных марок. Исследования высвобождения действующего вещества in vitro в сравнении с референтным препаратом проводили на приборе с проточной кюветой в соответствие с монографией ГФУ 2.9.42. Результаты. Проведены исследования физико-химических характеристик субстанции диклофенак натрия (микронизация, растворимость) и основы носителя твердый жир, которые влияют на высвобождение действующего вещества из лекарственной формы. Показатель «размер частиц» для двух образцов действующего вещества составил от 100 до 400 мкм и не более чем 15 мкм соответственно. Методом 2-факторного эксперимента разработан оптимальный состав суппозиториев. Определены условия проведения теста «Растворение»: объем среды (720 мл), температура растворения (37,0 ± 0,5) ºC, время отбор проб (15, 30, 45, 60, 90 мин.), среда растворения – буферный раствор с рН 7,4. Рассчитанный коэффициент подобия f2 составил 67, что свидетельствует о подобии профилей высвобождения и эквивалентности исследуемого препарата. Выводы. Исследованы фармако-технологические свойства диклофенака натрия и вспомогательного вещества твердый жир. Разработана методика высвобождения диклофенака натрия с использованием прибора с проточной кюветой в соответствии с требованиями ГФУ. Экспериментальным путем установлена степень высвобождения диклофенака натрия в среде растворения из суппозиториев ректальных как первый этап определения биодоступности. Установлена эквивалентность исследуемых образцов суппозиториев с референтным препаратом методом in vitro.
Розроблення складу та дослідження еквівалентності супозиторіїв із диклофенаком натрію методом in vitro з використанням тесту «Розчинення» для твердих ліпофільних дозованих форм
Разработка состава и исследования эквивалентности суппозиториев с диклофенаком натрия методом in vitro с использованием теста «Растворение» для твердых липофильных дозированных форм
Keywords: diclofenac sodium; suppositories; dissolution; flow-through cell; диклофенак натрію; супозиторії; розчинення; проточна комірка; диклофенак натрия; суппозитории; растворение; проточная кювета